O10.6 A Potent Combination Microbicide Gel Inhibits SHIV-RT, HSV-2 and HPV Infections in Vivo. (13th July 2013) - Kizima, L; Rodriguez, A; Kenney, J; Hsu, M; Derby, N; Mizenina, O; Menon, R; Zydowsky, T; Robbiani, M; Fernandez-Romero, J
Abstract : Background: HIV acquisition is fueled by infection with HSV-2 and HPV. Microbicides that target all three STIs may more effectively limit HIV incidence. We previously showed that a gel containing the NNRTI MIV-150, zinc acetate (Z) and carrageenan (C, MZC) significantly protected macaques from vaginal SHIV-RT challenge, while ZC also protected mice against HSV-2 vaginally and rectally. Here we evaluate a new formulation of MZC optimised for clinical use against SHIV-RT, HSV-2, and HPV. Methods: Toxicity was measured using the HSV-2 increased susceptibility model in mice. Macaques received gels vaginally every day for 14d followed by SHIV-RT (10 3 TCID50 ) 8 or 24h post-last gel or SHIV-RT plus HSV-2 (2 × 10 8 pfu) 8h post-last gel. Rectally, gels were applied 1h before SHIV-RT. Anti-HSV-2 and anti-HPV16 PsV activities were assessed by vaginally or rectally challenging mice with different viral doses 24h before to 8h after single gel application. Significance was determined by Fisher's exact or Mann Whitney U tests (P < 0.05). Results: MZC pretreatment did not enhance HSV-2 infection of mice. MZC protected macaques against vaginal SHIV-RT infection (in the presence or absence of HSV-2) for up to 8h (p < 0.0001 vs. C) and rectal SHIV-RT infection (0/5 MZC infected vs. 1/4 C; C barrier effect). While MZC only reduced vaginal HSV-2 infection of macaques by 27% after challenge with 2 × 108 pfu, MZC significantly reduced vaginal (p < 0.0001) and rectal (p = 0.0187) HSV-2 infection of mice when 106 pfu were applied immediately and also when 5 × 103 pfu were applied between 8h before and 2h after vaginal challenge (p < 0.0021). Protection of mice against HPV16 PsV was significant (p < 0.0001 vs. HEC) for MZC applied up to 24h before and 2h after challenge. Conclusion: MZC provides a durable window of protection against SHIV-RT, HSV-2, and HPV in vivo, making MZC an excellent candidate microbicide for clinical use.